1994
DOI: 10.3171/jns.1994.81.5.0656
|View full text |Cite
|
Sign up to set email alerts
|

Hunterian proximal arterial occlusion for giant aneurysms of the carotid circulation

Abstract: Hunterian proximal artery occlusion was used in the treatment of 160 of 335 patients harboring giant aneurysms of the anterior circulation. One hundred and thirty-three of these aneurysms arose from the internal carotid arteries, 20 from the middle cerebral arteries, and seven from the anterior cerebral arteries. Ninety percent of the patients had satisfactory outcomes. The safety of internal carotid artery occlusion has been greatly enhanced by preoperative flow studies and by test occlusion with an intracaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
102
0
5

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(107 citation statements)
references
References 4 publications
0
102
0
5
Order By: Relevance
“…Data from the era of surgical ICA clamp occlusion without previous tolerance testing indicate that approximately three-fourths of patients can tolerate ICA occlusion. [16][17][18] In our cohort, the angiographic test indicated tolerance to permanent ICA occlusion in two-thirds of patients, which indicates that the proportion of false-negatives is probably limited. After ICA occlusion, all aneurysms thrombosed completely except one, which makes the treatment very effective.…”
Section: Discussionmentioning
confidence: 77%
“…Data from the era of surgical ICA clamp occlusion without previous tolerance testing indicate that approximately three-fourths of patients can tolerate ICA occlusion. [16][17][18] In our cohort, the angiographic test indicated tolerance to permanent ICA occlusion in two-thirds of patients, which indicates that the proportion of false-negatives is probably limited. After ICA occlusion, all aneurysms thrombosed completely except one, which makes the treatment very effective.…”
Section: Discussionmentioning
confidence: 77%
“…13,14,16,18 Studies using endovascular deconstructive carotid occlusion have reported a morbidity and mortality rate ranging from 3% to 8%. [19][20][21][22][23] Although endovascular parent artery occlusion is a relatively easy and inexpensive technique with low morbidity in a selected population, the long-term consequences of altered hemodynamics should be considered.…”
Section: Treatment Options and Outcomesmentioning
confidence: 99%
“…5 Indeed, hunterian ligation is still used successfully in the treatment of many giant fusiform aneurysms. 5,6 Advances in surgical technique saw modest improvements in outcomes; however, the relative rarity and the frequent necessity for complex surgical reconstruction continue to test even the most experienced neurovascular surgeons. The advent of endovascular therapy and the more recent development of flow-diverting stents offered a promising method of treatment.…”
mentioning
confidence: 99%